2011
DOI: 10.1103/physrevlett.107.198101
|View full text |Cite
|
Sign up to set email alerts
|

Model System of Self-Reproducing Vesicles

Abstract: Development of self-reproducing vesicle systems is the first step for autopoietic cycles. We established a model self-reproducing vesicle system without the membrane molecule synthesis route. The model vesicle composed of cylinder- and inverse-cone-shaped lipids formed inclusion vesicles inside the mother vesicle, and the inclusion vesicles were then expelled by a temperature cycling. By changing the vesicle composition, the mother vesicles showed a budding-type self-reproduction pathway. A key concept of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 28 publications
2
59
0
Order By: Relevance
“…Precise strengths and direction of the imposed osmotic gradient and details of membrane chemical composition determine the types of deformations that ensue. Previously, comparable membrane deformations have been reported in GUVs by utilizing temperature as sources of external perturbations (Veatch and Keller, 2003a, 2005a,b; Veatch et al, 2006; Sakuma and Imai, 2011) or pH (Khalifat et al, 2008). It has also been shown that similar deformations can also be achieved by altering the membrane composition by incorporation of curvature-inducing sterols (Bacia et al, 2005) or selective solubilization using detergent interactions (Staneva et al, 2005; Muddana et al, 2012).…”
Section: Discussionmentioning
confidence: 56%
“…Precise strengths and direction of the imposed osmotic gradient and details of membrane chemical composition determine the types of deformations that ensue. Previously, comparable membrane deformations have been reported in GUVs by utilizing temperature as sources of external perturbations (Veatch and Keller, 2003a, 2005a,b; Veatch et al, 2006; Sakuma and Imai, 2011) or pH (Khalifat et al, 2008). It has also been shown that similar deformations can also be achieved by altering the membrane composition by incorporation of curvature-inducing sterols (Bacia et al, 2005) or selective solubilization using detergent interactions (Staneva et al, 2005; Muddana et al, 2012).…”
Section: Discussionmentioning
confidence: 56%
“…The order parameter P is calculated from the magnitude of the sample-averaged velocity orientations, see Eq. (13). Close to the transition, spatial inhomogeneities are usually observed in the form of density bands that travel perpendicularly to their elongation direction through a diluted disordered background (top right inset).…”
Section: Point-like Self-propelled Particlesmentioning
confidence: 99%
“…Surfactant molecules combine two antagonistic features on one building block: their head is usually hydrophilic, whereas their tail(s) is (are) mostly hydrophobic [9]. This leads, for instance, to the formation of closed bilayer membranes in the form of vesicles [10], with giant unilamellar vesicles (GUVs) as an extreme example (in reality, unlike the schematic, the layer thickness is orders of magnitude smaller than the radius) [11][12][13]. Polymers [3,14] in the simplest case can be treated as flexible linear chain-like objects.…”
Section: Introductionmentioning
confidence: 99%
“…These buds were pinched off of the mother vesicles by subsequent cooling below the transition temperature (Leirer et al 2009). By contrast, for DPPC vesicles with a low fraction of 1,2-dilauroyl-snglycero-3-phosphoethanolamine (DLPE), a heating-cooling cycle across the transition temperature induced only outerbud formation and abscission (Sakuma and Imai 2011). For high DLPE fractions, a similar temperature cycle resulted in the formation of inward buds that were ejaculated by 'birthing' out of the mother vesicle due to inner pressure buildup that resulted in the formation of transient pores in the mother vesicle membrane (see Fig.…”
Section: Division Processes Based On Physical Mechanismsmentioning
confidence: 99%